Ungendering power relations: stateswomen, agency and foreign policy in Jordan - Guzzi, Catherine (AUC Knowledge Fountain, 2012)
Feminist international reFeminist international relations theory argues that womenâ s marginalization in world affairs both results from and is sustained by a gendering of international relations in which the norms of power, aggression, and self-help typically associated with masculinity dominate IR theory and practice. While gender has become an accepted topic within international relations, a coherent argument for how gendered relationships of power exist within and outside states and how they affect international relations has yet to be made. Little effort has been made to move beyond theory and examine the ways in which gender affects particular cases and issues. This thesis studies the role of women in the foreign policy process of the Hashemite Kingdom of Jordan to test the validity of feminist theory to contemporary IR. Within a triple-layered theoretical framework of feminist IR, the English Schoolâ s world and international societies, and the role of the family in the Middle East, womenâ s agency, their views on security, and their values/norms are observed in order to better understand the role of gender in international relations as well as the role of women in the Middle East. Through a series of semi-structured interviews conducted in Amman, Jordan, it was found that Jordanian stateswomen do have agency within the monarchyâ s foreign policy process. Furthermore, they feel they can freely express their values/norms without having to â play the manâ s gameâ and mimic patriarchal values. However, the institutional identity of the Jordanian Ministry of Foreign Affairs attracts men and women with similar values and opinions, making a variation of policy preferences difficult to measure. Gender, it seems, affects international relations more at the systemic level whereby state behavior reflects typical norms of hegemonic masculinity or femininity. Further studies on womenâ s agency in other institutions as well as the gendered behaviors of states could shed more light on the role of gender in international relations.